Antioxidant Face Cream Formulation of Ethanol Extract from Soursop leaves (Annona muricata L) - Putriana Rahman, Alief; Liana, Liana; H, Syaifiyatul (Berkala Ilmiah Kimia Farmasi, 2022)
Face cream was a treatment cream used to treat facial skin. One of the natural plant ingredients that could be used as an active substance in cream preparations was soursop leaves (Annona muricata L.), which had antioxidant activity. The purpose of this study was to formulate cream preparations from soursop leaf ethanol extract and test the antioxidant activity on face cream preparations. Soursop leaves were extracted by maceration using a 96% ethanol solvent. Cream preparations in physical quality evaluation included organoleptic test, pH test, homogeneity test, viscosity test, spread power test, sticking power test, centrifugation test, and determination of emulsion type and antioxidant activity test with DPPH method, measured at a wavelength of 511,5 nm using UV-Vis spectrophotometry. The results of this study produced a face cream preparation of soursop leaf ethanol extract with differences in color in organoleptic cream preparations. pH tests of FI, FII, and FIII creams had an average yield of 6,0-6,6. The homogeneity tests of FI, FII, and FIII showed homogeneous results. The viscosity test had a value of 49950 cPs. The FI, FII, and FIII spread power tests had good results with an average of 5,2-5,7 cm. FI, FII, and FIII sticking power tests had an average value of 26,5-46,5 seconds. FI, FII, and FIII centrifugation tests were physically stable, and the determination of the type of cream emulsion was type M/A. Testing the antioxidant activity of facial cream with ethanol extract of soursop leaves in FI with a concentration of 3% showed an IC50 value of 80,64 ppm, FII with a concentration of 5% showed an IC50 value of 46,06 ppm, and FIII with a concentration of 7% showed an IC50 value of 10,91 ppm. Based on the results of the study, it could be concluded that the preparation of facial cream with ethanol extract of soursop leaves in FI, FII, and FIII met the physical stability requirements based on organoleptic test parameters, pH test, homogeneity test, viscosity test, spread power test, sticking power test, centrifugation test, and determination of emulsion type. FI cream preparations had an IC50 value of 80,64 ppm, indicating strong antioxidant activity, FII had an IC50 value of 46.06 ppm, indicating very strong antioxidant activity, and FIII had an IC50 value of 10,91 ppm, indicating very strong antioxidant activity.Keywords: Cream, Formulation, Antioxidant, Ekstrak, Soursop Leaves